APPLICATION OF DISCOVERY LEARNING METHOD LEARNING TO WRITING PROCEDURE TEXT IN VOCATIONAL SCHOOL STUDENTS 1 SOREANG - Riska Rahayu; Ika Mustika (JLER (Journal of Language Education Research), 2021)
This study aims to determine the writing results of class XI students of SMK Negeri 1 Soreang in learning to write procedural texts by applying the discovery method learning students can identify the procedural text and the content contained in the procedural text either oral or written in a creative, collaborative, and responsible way, full of love for the country and gratitude. The method that researchers use is the experimental method. The pre-experimental research design used was a one-group pretest-posttest design. This design consists of one group that is given a pretest to determine the ability of students before being given treatment. The sample of this research is class XI Elektro 1 with a total of 30 students. Data collection techniques that researchers use in research in the initial test (pretest) and the final test (posttest). Based on the research results, it can be seen from the data processing the ability to write procedural texts before using the discovery learning method, the mean value of the pre-test (pretest) was 59.75 and after using the discovery learning method, the average value of the final test (posttest) was 83, 75. So, it can be concluded that the application of the discovery learning method to learning to write procedural texts has been able to improve student learning outcomes.